Correction to: A pain relieving reimbursement program? Effects of a value-based reimbursement program on patient reported outcome measures - Thérèse Eriksson; Hans Tropp; Ann-Britt Wiréhn; Lars-Åke Levin (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.